2020
DOI: 10.1177/1012690219894885
|View full text |Cite
|
Sign up to set email alerts
|

‘You’re going to teach my son to be viado’: From ‘girling’ to queering sport for development?

Abstract: This paper critically explores how queer youth experience sport for development programmes in Brazil. Whilst the Sport for Development and Peace (SDP) field is not void of discussions that touch upon heteronormativity and sexuality, the ‘sensitive’ stories of lesbian, gay, bisexual and transgender (LGBT) individuals within SDP initiatives remain rather unheard. Drawing on ethnographic methodology and queer theory, this paper aims to understand the impact of two different SDP programmes located in Sao Paulo, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
5
0
2
Order By: Relevance
“…Their lack of a personal history in physical education or sport coaching courses may have enabled these SWs to focus on relationship building that could produce enjoyment rather than emphasizing achievement in progressions of skill development and competitions as may occur in SfD projects (e.g. Kidd 2011;Válková 2021;Zipp, Smith, and Darnell 2019). The findings suggest staff members for SfD need to engage in critical self-reflection to grasp how their previous training and curricular background could enhance or detract from relationship building with participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their lack of a personal history in physical education or sport coaching courses may have enabled these SWs to focus on relationship building that could produce enjoyment rather than emphasizing achievement in progressions of skill development and competitions as may occur in SfD projects (e.g. Kidd 2011;Válková 2021;Zipp, Smith, and Darnell 2019). The findings suggest staff members for SfD need to engage in critical self-reflection to grasp how their previous training and curricular background could enhance or detract from relationship building with participants.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarship focusing on SfD projects, including those for refugees, reveals that the focus of many such projects has often been on the learning of sport skills, on using sport to develop life skills, on empowerment, on guiding youth towards sport club membership, on enhancing the integration of refugees into the country where the refugees hope to live/settle and on contributing to the wellbeing of participants (Kaya et al 2021;Kidd 2011;Schulenkorf, Sherry, and Rowe 2016;Spaaij and Jeanes 2013;Spaaij et al 2019;Válková 2021;Welty Peachey and Burton 2017;Welty Peachey, Schulenkorf, and Hill 2020;Zipp, Smith, and Darnell 2019). Kaya et al (2021) found however, that immigrant and young refugees did not have long term goals for participation in such projects but participated in sport because they viewed it as a fun activity that gave them an opportunity to interact with others in an enjoyable way.…”
mentioning
confidence: 99%
“…Future studies applying more focused and systematic strategies to document existing multilevel factors within the local context of participants’ daily lives can form an important foundation for developing intervention strategies to address barriers and leverage support. Such efforts may be particularly suited to include additional critical perspectives currently overlooked in this field, with emphases on emergent areas such as intersectionality (i.e., how overlapping social identities may compound experiences of discrimination within sport) [ 47 ], engagement of girls and women beyond heteronormative conceptions (e.g., inclusion of lesbian, gay, bisexual and transgender experiences) [ 48 ], and approaches customized for displaced women and girls [ 49 ]. Additional research is also needed to reveal experiences and perspectives of sport participation by women across the life course [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…La mixité ne doit pas être vue comme une solution miracle aux problèmes d'inclusion, mais comme un outil auquel il faut réfléchir. D'autres vont plus loin en insistant pour dire qu'un réel changement de paradigme vers un sport queer inclusif, qui remettrait en question la nécessité des différenciations de genre, est nécessaire (Landi, 2018(Landi, , 2019Larsson et al, 2014 ;Válková, 2020).…”
Section: Personnes De La Communauté Lgbtq2+ 17unclassified